Urban magnetism:understanding cities through the lens of geo-tagged photography - Paldino, Silvia; Pantano, Pietro; Sobolevsky, Stanislav (My University, 2016)
This research work presents a method for a new mapping process, based on social networks (especially geo-referred pictures downloaded from the websites of photosharing) to work alongside the maps commonly used in spatial planning. In the vast world of social, I choose to consider in particular the photographs, because people choose to photograph specific places or times that they consider important for some reasons. This would allow a truly innovative reading of the territory, making the concept of smart city in its dual aspects: the technological (because they take into account the social networks by creating dynamic maps of the territories) and human (because it takes into account the actual participation and objective citizens and more generally of land users, without the burden of being directly involved, but only through the daily activities that each of us carries on social networks). In this way it is possible to monitor urban areas that should be protected, managed, potentiated, discovered, making liveble and lived all the city and the territory to have smarter and safer city.
Scuola di dottorato"Archimede" Scienze e Tecnologie dei Sistemi Complessi, Ciclo XXVIII, a.a. 2015-2016
Keywords: GIS<Geographic information systems>; Complex sistemy; City smart